2022
DOI: 10.1177/00031348221146975
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lymph Node Metastasis and Recurrence in T1 Colorectal Cancer: Analysis of 801 Patients in a Single Institute

Abstract: Objective To identify risk factors for lymph node metastasis and postoperative recurrence of pT1 colorectal cancer by clinicopathological study of surgically resected cases. Methods In 801 patients with pT1 colorectal cancer who underwent surgical resection with lymph node dissection between April 2007 and January 2021, we evaluated clinicopathological factors (age, gender, BMI, serum CEA level, tumor localization, additional resection after endoscopic treatment, operation time, blood loss, histological type, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…With regard to the analysis of clinicopathologic factors, the results of this study suggested that independent risk factors for LNM in CRC included poorer histologic grade, LVI and CEA; in addition, histologic grade (G3), histologic grade (mucin-producing subtype), depth of invasion(T3-T4), and LVI were associated with poor prognosis. The above results were consistent with previous studies ( 32 35 ). The consensus molecular subtypes (CMS) of colorectal cancer indicated that the metabolic subtype (CMS3) potentially associated with Man metabolism and mucinous differentiation ( 36 ).…”
Section: Discussionsupporting
confidence: 94%
“…With regard to the analysis of clinicopathologic factors, the results of this study suggested that independent risk factors for LNM in CRC included poorer histologic grade, LVI and CEA; in addition, histologic grade (G3), histologic grade (mucin-producing subtype), depth of invasion(T3-T4), and LVI were associated with poor prognosis. The above results were consistent with previous studies ( 32 35 ). The consensus molecular subtypes (CMS) of colorectal cancer indicated that the metabolic subtype (CMS3) potentially associated with Man metabolism and mucinous differentiation ( 36 ).…”
Section: Discussionsupporting
confidence: 94%
“…Among the nine single institutions, the least differentiation analysis was used in four, the predominant differentiation analysis was adopted in four, and the method used in the remaining one institution was unclear. 8,[16][17][18][20][21][22][23]25 When classified by the predominant differentiation analysis, 0.8% (8/971) of the cohort was defined as high-grade in the present study which is equal to the 0.6%-5.0% found in the previous studies with the predominant differentiation analysis. 16,20,22,23 It suggests that this method may lack the sensitivity to act as a risk factor.…”
Section: Discussionsupporting
confidence: 47%
“…However, the assessment of tumor grade according to the least or predominant component actually depends on the institution in Japan (Table 1). Among the nine single institutions, the least differentiation analysis was used in four, the predominant differentiation analysis was adopted in four, and the method used in the remaining one institution was unclear 8,16–18,20–23,25 . When classified by the predominant differentiation analysis, 0.8% (8/971) of the cohort was defined as high‐grade in the present study which is equal to the 0.6%–5.0% found in the previous studies with the predominant differentiation analysis 16,20,22,23 .…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations